Digital governance: A conceptual framework and research agenda - Hanisch, Marvin; Goldsby, Curtis M.; Fabian, Nicolai E.; Oehmichen, Jana (Journal of business research, 2023)
•We introduce digital governance as a distinct form of governance.•We shed light on mechanisms of digital governance in terms of control, coordination, incentives, and trust.•We distinguish between analog, augmented, and automated forms of governance.•We predict that high transactivity favors augmented and automated forms of governance.•We present opportunities for future research related to digital governance. The rapid expansion of digital technologies has paved the way for new forms of organizing, facilitated by increased data and knowledge exchange between individuals and organizations. However, this poses major new challenges for designing effective governance mechanisms. This paper highlights the critical role of digital governance in facilitating digitally enabled exchange relationships. To this end, we propose a typology of analog, augmented, and automated governance modes, each associated with specific control, coordination, incentive, and trust mechanisms. Additionally, we provide a heuristic for determining the optimal governance choice via the interplay of transactivity (i.e.,the contributors, connections, and consistency in an exchange network) and corresponding governance costs. Our study advances the governance literature by defining digital governance as a distinct form and outlining key governance mechanisms and choices in the digital era. Finally, we identify avenues for future research in this field.